Vacuum-Assisted Closure and Muscle Flap as An Alternative Modality for Infected Wound After Orif of Tibial Fracture: Case Report - OK Ilham Abdullah Irsyam; Saraswati Hastika; Hendra Hendra; Andrew Budiartha Budisantoso; Tesar Akbar Nugraha (Journal Orthopaedi and Traumatology Surabaya)
Background: The blood supply of a bone can be decreased due to the use of an implant, leading to wound-bed bacterial colonization and the development of the SSI. The principle of vacuum-assisted closure (VAC) is to use a negative pressure environment in the wound to promote increased wound healing. The case shows that VAC application and muscle flap therapy provide the definitive healing of infected wounds after ORIF.